The Future of Digital Education: Artificial Intelligence, the Metaverse, and the Transformation of Education - Tolga Yıldız (İstanbul Üniversitesi Sosyoloji Dergisi)
This article examines the historical evolution of education, highlighting significant shifts shaped by sociocultural dynamics and technological advancements. In early human societies, education was an organic process, rooted in communal activities essential for survival. As societies progressed, education became more structured, serving not only as a tool for intellectual development but also as a means to reinforce social hierarchies, particularly during the Ancient Greek period and the Middle Ages. The Industrial Revolution marked a transformative shift, where education systems were standardised to meet the needs of an industrialised society, mirroring the factory environment to instil discipline and conformity. The introduction of radio and television in the 20th century further democratised education, making it more accessible and blurring the boundaries between traditional educational settings and daily life. The article underscores how digital technologies, especially the internet, have revolutionised education by introducing new modes of learning through different Web eras. These advancements have shifted education from static, one-size-fits-all models to more interactive and personalised learning environments. The rise of AI and the metaverse promises even greater customisation and immersive experiences in the learning process. However, the integration of these technologies also raises important ethical, social, and developmental challenges, particularly in terms of equity, accessibility, and the potential erosion of human connection in education. The article advocates for a balanced approach to digital education, ensuring that technological progress enhances rather than detracts from the holistic development of learners.